Exploring Fungicide Sensitivity in Soybean Stem Blight Pathogen Diaporthe longicolla, Emphasizing Genetic Variability Impact on Response to SDHI Fungicides Fluopyram and Pydiflumetofen - Shanshan Chen; Zhanyun Liu; Zhengjie Chang; Yuxin Zheng; Xueyang Wang; Ningwei Li; Zhongqiao Huang; Can Zhang; Xili Liu (Journal of Fungi)
Diaporthe species are critical plant pathogens that contribute to a disease complex responsible for substantial yield losses in soybean production worldwide. However, reports on the primary Diaporthe species causing soybean stem blight and their sensitivity to various fungicides are scarce in China. In this study, a total of 46 D. longicolla strains were isolated and identified from diseased soybean stems and rots collected from 14 regions of Heilongjiang province in 2021 and 2022. Among the eight fungicides examined, fludioxonil, mefentrifluconazole, tebuconazole, and azoxystrobin demonstrated effective inhibition for D. longicolla, with EC50 values < 0.3 µg/mL. Interestingly, the EC50 values of D. longicolla to two succinate dehydrogenase inhibitors (SDHIs), pydiflumetofen and fluopyram, were 5.47 µg/mL and over 100 µg/mL, respectively. In molecular dynamics simulations, pydiflumetofen exhibited a smaller RMSD, while fluopyram had a higher binding free energy with Sdh proteins compared to pydiflumetofen. This difference may contribute to the higher activity of pydiflumetofen in D. longicolla. Further analysis of the electrostatic potential and structural conformations of the binding pocket revealed that pydiflumetofen formed more hydrophobic interactions with SdhC and SdhD and was positioned closer to the SdhD subunit. A mixture of fludioxonil and mefentrifluconazole at a ratio of 1:5, as well as fludioxonil and pydiflumetofen at a ratio of 1:5, exhibited synergistic effects. These findings demonstrated that several fungicides could be utilized to control Diaporthe stem blight, and the difference in binding affinity to the Sdh subunit impacts sensitivity to fluopyram and pydiflumetofen.